Quantum theory of isomeric excitation of ^{229}Th in strong laser fields - Wu Wang; Xu Wang (Physical Review Research, 2023)
A general quantum mechanical theory is developed for the isomeric excitation of ^{229}Th in strong femtosecond laser pulses. The theory describes the tripartite interaction between the nucleus, the atomic electrons, and the laser field. The nucleus can be excited both by the laser field and by laser-driven electronic transitions. Numerical results show that strong femtosecond laser pulses are very efficient in exciting the ^{229}Th nucleus, yielding nuclear excitation probabilities on the order of 10^{−11} per nucleus per pulse. Laser-driven electronic excitations are found to be more efficient than direct optical excitations.